2017
DOI: 10.1186/s12889-017-4537-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of domestic waste management and related health outcomes in Sunyani, Ghana: a protocol towards enhancing policy

Abstract: BackgroundDomestic waste generation has contributed significantly to hampering national waste management efforts. It poses serious threat to national development and requires proper treatment and management within and outside households. The problem of improper waste management has always been a challenge in Ghana, compelling several national surveys to report on the practice of waste management. However, little is known about how much waste is generated and managed within households and there is a serious dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 36 publications
(39 reference statements)
1
16
0
1
Order By: Relevance
“…Our finding agrees with the study by Vassanadumrongdee and Kittipongvises (2018) which found that age and family with children have a positive influence on respondent's source separation. Age was also a determinant factor in waste management practices in other studies [ 2 , 15 ]. With aging and married respondents, this could be highly related to the increasing sense of responsibility towards the environment and the importance of increasing the quality of life among household members.…”
Section: Discussionmentioning
confidence: 85%
“…Our finding agrees with the study by Vassanadumrongdee and Kittipongvises (2018) which found that age and family with children have a positive influence on respondent's source separation. Age was also a determinant factor in waste management practices in other studies [ 2 , 15 ]. With aging and married respondents, this could be highly related to the increasing sense of responsibility towards the environment and the importance of increasing the quality of life among household members.…”
Section: Discussionmentioning
confidence: 85%
“…7 Even though the government has made regulations on waste management, the majority of people do not practice waste management. 8 Most of the local governments handle their solid waste just by collecting, transporting and dumping to landfill. Currently, reduce, reuse and recycle (3R) activities are not optimally practiced.…”
Section: Resultsmentioning
confidence: 99%
“…Similar findings have been reported in previous studies. 14,15 The authorities should be encouraged to promote environmental information and counseling to the community, because the extent to which people participate effectively, especially women, can only be improved through education and counseling. If garbage is collected by garbage collectors, the costs should be designed to be accessible to low-income communities.…”
Section: Discussionmentioning
confidence: 99%
“…To predict participants' knowledge of the causes of disease from waste management, five predictors in this model: age, sex, marital status, education level, and household income. 6,14 For the questionnaire component, items and reliability were applied. Statistical significance is set at ≤0.05.…”
Section: Methodsmentioning
confidence: 99%